Ions and Organic Solutes as Implicated in the Ameliorative Effect of Exogenous Application of Calcium on Salt Stressed Tomato Plants - Henry, Matieu; SOSSA, Elvire Line; Noumavo, Agossou Daniel Pacôme; AMADJI, GUILLAUME LUCIEN; BABA-MOUSSA, LAMINE; GANDONOU, Christophe (My University, 2021)
Aims: This study evaluated the role of sodium, potassium, proline and soluble sugars accumulation in the ameliorative effect of an exogenous application of calcium on the detrimental effect of salinity on tomato plants. Study Design: The experiment was implemented as a Completely Randomized Design (RCD) with four treatments and three replications. Place and Duration of Study: The experiment was realized in a green house of the Faculty of Agronomical Sciences, University of Abomey-Calavi, Benin Republic from June to July 2020. Methodology: Three weeks old plants of the tomato cultivar “Padma” was submitted in pots to four treatments comprising the control (without NaCl); salt stress (120 mM NaCl) and a combination of 120 mM NaCl and exogenous application of 40 mM CaSO4 or Ca (NO3)2 by irrigation every two days. Plants growth, sodium (Na) and potassium (K) as well as proline and soluble sugars contents of leaves and roots were determined after two weeks. Results: Salt effect reduced significantly plant growth at P =.05, root K content at P =.05 and leaf K/Na ratio at P =.01 whereas it increased significantly leaf Na at P =.05 and root soluble sugars content at P =.05. The application of exogenous calcium (Ca) induced a significant amelioration of plant growth at P =.01 more marked with CaSO4 than with Ca (NO3)2. This treatment induced a significant decrease at P =.01 in leaf and root Na content and a significant increase at P =.05 in root K content only for CaSO4, a significant increase at P =.01 in leaf K/Na ratio and a significant increase at P =.01 in leaf and root proline content only for Ca(NO3)2. Conclusion: The ameliorative effect of both forms of calcium was due mainly to sodium (Na) exclusion from leaves and potassium (K) accumulation associated to a maintain of high K/Na ratio mainly in leaves. The importance of proline accumulation as an indicator of this ameliorative effect was associated only to Ca(NO3)2.
Keywords: Ameliorative effect; calcium nitrate; calcium sulphate; proline; salt stress mitigation; sodium chloride; soluble sugars